1987
DOI: 10.1073/pnas.84.24.9175
|View full text |Cite
|
Sign up to set email alerts
|

Identification, purification, and characterization of a mast cell-associated cytolytic factor related to tumor necrosis factor.

Abstract: The role of mast cells and mast-cell-derived factors in natural cytotoxic reactions was investigated. Cultured and freshly isolated murine mast cells are shown to be cytotoxic to WEHI-164 and YAC-1 targets in 18-hr viability assays but not in 4-hr assays. Here, we describe a cytotoxic factor in murine mast cells that is immunologically related to tumor necrosis factor (TNF). This TNF-like factor lyses WEHI-164 cells with a slow time course requiring 16-20 hr for the lytic reaction to complete. Antibodies speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(111 citation statements)
references
References 28 publications
1
110
0
Order By: Relevance
“…Antihistamines will decrease plasma leakage during immune complex reactions (34). It has recently been reported that mast cells upon stimulation with a number of agents, including IgE/Ag, calcium ionophore, and PMA, will cause the induction of various cytokines, such as IL-1, IL-3, IL-4, IL-6, GM-CSF, and TNFa (35)(36)(37) (42).…”
Section: Methodsmentioning
confidence: 99%
“…Antihistamines will decrease plasma leakage during immune complex reactions (34). It has recently been reported that mast cells upon stimulation with a number of agents, including IgE/Ag, calcium ionophore, and PMA, will cause the induction of various cytokines, such as IL-1, IL-3, IL-4, IL-6, GM-CSF, and TNFa (35)(36)(37) (42).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, although the major source of this cytokine is macrophages (Beutler & Cerami, 1987;Aggarwel et al, 1985), the molecule can also be released by other cell types. These include monocytes stimulated by gamma interferon (Beutler & Cerami, 1987), T lymphocytes and T cell lines following stimulation with phorbol esters and anti-CD3 antibodies in different combinations (Granger & Williams, 1968;Cutri et al, 1987;Scheurich et al, 1987;Sung et al, 1988a;Turner et al, 1987), B lymphocytes (Williamson et al, 1983;Sung et al, 1988b), large granular lymphocytes (Ostensen et al, 1987;Peters et al, 1986) and mast cells (Young et al, 1987).…”
Section: General Properties Of Tnfmentioning
confidence: 99%
“…Bone marrow-derived MC line was prepared from BALB/c mice as reported [14,15]. Cells were grown in DMEM supplemented with 10% FCS, antibiotics, and 0.1% mercaptoethanol and passaged every other day to keep their concentration in the range of 0.3 to 0.5 ϫ 10 6 /mL.…”
Section: Use Of C1mc/c571 Murine MC Linementioning
confidence: 99%